Intergroup Relations in Latin America: Intergroup Contact, Common Ingroup Identity, and Activism among Indigenous Groups in Mexico and Chile. (3rd June 2016) - Çakal, Huseyin; Eller, Anja; Sirlopú, David; Pérez, Andrés
Abstract : In two correlational studies in Mexico (Study 1: N = 152, Mexican Indigenous people) and Chile (Study 2: N = 185, Chilean Indigenous people, Mapuche), we investigated how different dimensions of common ingroup identity (CII) and intergroup contact between Indigenous people influence activist tendencies and how past participation moderates this influence. In Study 1, CII as Mexican and intragroup contact between Indigenous people predicted activist tendencies via increased group efficacy. In Study 2, CII as Chilean positively predicted normative activism both directly and via group efficacy. In both studies intragroup contact between Indigenous people directly and positively predicted future intentions to engage in political action and past activism moderated these associations. These findings suggest that the negative effects of CII on activism do not readily map onto contexts where subgroup and CII overlap, and contact might have beneficial effects on activism. Implications for future research and policy are discussed.